1990
DOI: 10.1007/bf02779182
|View full text |Cite
|
Sign up to set email alerts
|

Disorders of bone metabolism caused by small bowel resection in rats

Abstract: Disorders of bone metabolism caused by resection of three quarters of the small bowel in rats were investigated biochemically and histomorphologically. Metabolic bone disorders developing 90 days after in 75%-distal-small-bowel resected rats were characterized by reduction in ash content of the femur and by the disappearance of the trabecular bone in tibial metaphysis. Biochemical studies showed significant decrease in serum Ca and 1,25-dihydroxyvitamin D concentrations in 75% distal small bowel resected rats.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Insoluble calcium soaps may be produced from the fatty acids present in faeces as a result of impaired fat absorption21. Although the resection technique used in the present study was more extensive than that described by Uno et al 20, hypocalcaemia or hyperparathyroidism was not observed after total jejunoileal resection. Severe growth retardation was observed after jejunoileal resection, but the animals did not develop steatorrhoea or cancellous bone osteopenia.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Insoluble calcium soaps may be produced from the fatty acids present in faeces as a result of impaired fat absorption21. Although the resection technique used in the present study was more extensive than that described by Uno et al 20, hypocalcaemia or hyperparathyroidism was not observed after total jejunoileal resection. Severe growth retardation was observed after jejunoileal resection, but the animals did not develop steatorrhoea or cancellous bone osteopenia.…”
Section: Discussionmentioning
confidence: 61%
“…In contrast to the present results, severe disturbances in calcium metabolism and bone mineralization after extended bowel resection have been noted by others. Uno et al 20 showed a negative calcium balance and a marked decrease in trabecular bone in rats after a 75 per cent distal small bowel resection. Their data suggest that suppressed intestinal calcium absorption is an important cause of disorders of bone metabolism in short bowel syndrome.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation